2019
DOI: 10.18551/rjoas.2019-11.13
|View full text |Cite
|
Sign up to set email alerts
|

Informal Sector – A Survival or Consolidation Livelihood Strategy: A Case Study of the Informal Sector Entrepreneurs in Palembang City, Indonesia

Abstract: The informal sector is inseparable from the population of Indonesia. Since the 1998 crisis, it has been the source of life for many people. Moreover, in the current era of demographic dividend, it becomes, albeit subsistent, the most popular survival livelihood strategy. This study aimed (1) to investigate and elaborate whether or not the informal sector was included in the survival or consolidation livelihood strategy and (2) to describe how this sector potentially transitioned from the survival livelihood st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
3
1
0
5
Order By: Relevance
“…More than half of the respondents have graduated from senior high school education or equivalent, even the proportion of respondents who have graduated from university is the second highest. This finding is consistent with the statement that the informal sector is in demand not only by groups with low education status but also by those with better education status (Armansyah et al 2019 ). Besides, BPS data showed that the open unemployment rate in this area was dominated by people with high school education or equivalent with a proportion of 28.1% in 2019.…”
Section: Resultssupporting
confidence: 92%
“…More than half of the respondents have graduated from senior high school education or equivalent, even the proportion of respondents who have graduated from university is the second highest. This finding is consistent with the statement that the informal sector is in demand not only by groups with low education status but also by those with better education status (Armansyah et al 2019 ). Besides, BPS data showed that the open unemployment rate in this area was dominated by people with high school education or equivalent with a proportion of 28.1% in 2019.…”
Section: Resultssupporting
confidence: 92%
“…The existence of street vendors with an academic/diploma/university as their last education level which was included in the group with a survival strategy shows that education does not always influence livelihood strategies. This is in line with a study conducted by Armansyah et al that the final education level of street vendors did not necessarily improve their livelihood strategies [17].…”
Section: The Relationship Between Characteristics Of Street Vendors and Their Livelihood Strategiessupporting
confidence: 91%
“…Also, the absence of street vendors who were included in the accumulation strategy shows that the COVID-19 pandemic has greatly impacted the lives of street vendors. The results were in line with a study conducted by Armansyah et al which confirms that street vendors in normal conditions are dominated by groups with survival strategies and it is difficult to improve their livelihood strategies, i.e., to enter into a consolidation strategy [17]. Table 3 shows that 61 street vendors who prioritized food needs, four street vendors who did side jobs, and 39 street vendors who used social assistance.…”
Section: Livelihood Strategies Performed By Street Vendors During the Covid-19 Pandemicsupporting
confidence: 88%
“…Sependapat dengan pernyataan tersebut, pola bertahan hidup pekerja informal terutama kaum miskin kota yakni mengembangkan ekonomi atau produksi subsisten merupakan upaya yang paling rasional guna mempertahankan bertahan hidup (Evers, 1991;Haryanto, S, 2016;Hayat, 2012). Studi lain yang dilakukan Armansyah, et.al (2019) terhadap pekerja perempuan di sektor informal di Kota Palembang bahwa mengharapkan bantuan berupa dengan memanfaatkan aset sosial seperti hubungan keluarga atau pertemanan dan uang berupa pinjaman adalah cara untuk bertahan hidup karena tidak memiliki aset seperti keahlian, pendidikan, modal ataupun teknologi.…”
Section: Menelaah Dampak Terhadap Pendapatanunclassified